Initiation of combined antiretroviral therapy confers suboptimal beneficial effects on neurovascular function in people with HIV - Singh, Meera V.; Uddin, Md Nasir; Singh, Vir B.; Peterson, Angelique N.; Murray, Kyle D.; Zhuang, Yuchuan; Tyrell, Alicia; Wang, Lu; Tivarus, Madalina E.; Zhong, Jianhui; Qiu, Xing; Schifitto, Giovanni (Frontiers in Neurology, 2023)
This study examined the effects of acute and chronic combination antiretroviral therapy (cART) on brain neurovascular function assessed by magnetic resonance imaging (MRI) in people with HIV (PWH). We enrolled 35 treatment-naïve PWH and 53 HIV negative controls (HC). Study participants underwent T1-weighted anatomical, pseudo-continuous arterial spin labeling, and resting-state functional MRI to obtain measures of cerebral blood flow (CBF) and cerebrovascular reactivity (CVR) prior to starting cART treatment and at two-time points (12 weeks and two years) post-cART initiation. Controls were scanned at the baseline and 2-year visits. We also measured plasma levels of microparticles of endothelial and glial origin and well-known endothelial inflammation markers, ICAM-1 and VCAM-1, to assess HIV-associated endothelial inflammation and the interaction of these peripheral markers with brain neurovascular function. Results indicate that HIV infection is associated with reduced CVR and increased levels of endothelial and glial microparticles (MPs) prior to initiation of cART. Further, CVR correlated negatively with peripheral MP levels in PWH. Our results suggest that cART treatment has a beneficial effect on the neurovascular function. However, these benefits are suboptimal over time.